The Issue of Religion during the Bolshevik ERA (1917-1939) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, the relationship between religion and the state during the Bolshevik era is analyzed, highlighting the ideological conflict between the Bolshevik regime, which promoted atheism and aimed to build a secular, socialist state, and the traditional religious institutions that had significant influence in society. Additionally, the article discusses how religious practices were suppressed, the strategies employed by the Bolsheviks to weaken the power of religious organizations, and the resistance from religious communities.